Buried remnants of the Laurentide Ice Sheet and connections to its surface elevation - Lacelle, Denis; Fisher, David A.; Coulombe, Stéphanie; Fortier, Daniel; Frappier, Roxanne (Université d'Ottawa | University of Ottawa, 2018)
The Laurentide Ice Sheet (LIS) occupied a large part of North-America during the late Pleistocene. Determining the proper surface geometry and elevation of the LIS is of central importance to estimate global changes in sea-level and atmospheric circulation patterns during the late Pleistocene and Holocene. Despite largely disappearing from the landscape during the late Holocene, LIS remnants are found in the Penny and Barnes ice caps on Baffin Island (Canada) and ongoing permafrost degradation has been exposing relics of the LIS buried along its northern margin since the late Pleistocene. Here, we use the δ18O records of six LIS remnants and the late Pleistocene δ18O-elevation relation to establish ice elevation in their source area during the last glacial maximum (LGM). Contrary to some modeled reconstructions, our findings indicate an asymmetric LIS topography with higher ice on Keewatin Dome (~3200 m) and thinner ice in the prairies along the Plains divide (1700-2100 m) during LGM. The resiliency of icy permafrost to past warm intervals preserved relics of the LIS; these ice-marginal landscapes, now poised for thaw, should uncover more valuable clues about the conditions of the last major ice sheet on Earth.